Validation of an enzyme-linked immunosorbent assay that detects Histoplasma capsulatum antigenuria in colombian patients with AIDS for diagnosis and follow-up during therapy (2014)
We validated an antigen capture enzyme-linked immunosorbent assay (ELISA) in Colombian persons with AIDS and proven histoplasmosis and evaluated the correlation between antigenuria and clinical improvement during follow-up. The sensitivity of the Histoplasma capsulatum ELISA was 86%, and the overall specificity was 94%. The antigen test successfully monitored the response to therapy. Copyright © 2014, American Society for Microbiology. All Rights Reserved.